How software works - White, Ron; Wattenmaker, Pamela Drury (Emeryville, California : Ziff-Davis Press, 1993)
A guide to the functions and operation of computer software explains how software and hardware work together, discussing operating systems, programming languages, and database, spreadsheet, word processing, graphics, communications, Windows, and utility software products. Original.
Introduction -- Part 1. How Hardware and Software Work Together -- Part 2. How Programming Languages Work -- Part 3. How Databases Work -- Part 4. How Spreadsheet Software Works -- Part 5. How Word Processors Work -- Part 6. How Graphics Software Works -- Part 7. How Communications Software Works -- Part 8. How Windows Works.
Includes index.
Keywords: COMPUTER SOFTWARE